2016
DOI: 10.7150/ijbs.13453
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of epithelial to mesenchymal transition and upregulation of let 7b are critically involved in ursolic acid induced apoptosis in malignant mesothelioma cell

Abstract: Malignant pleural mesothelioma (MPN), which is caused by asbestos exposure, is one of aggressive lung tumors. In the present study, we elucidated the anti-tumor mechanism of ursolic acid in malignant mesotheliomas. Ursolic acid significantly exerted cytotoxicity in a time and dose dependent manner in H28, H2452 and MSTO-211H mesothelioma cells and inhibited cell proliferation by colony formation assay in a dose-dependent fashion. Also, ursolic acid treatment accumulated the sub-G1 population, attenuated the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 45 publications
2
34
0
Order By: Relevance
“…62 Other study has reported that suppressed EMT through attenuation of AKT phosphorylation and βcatenin. 63 Our results also indicated that foretinib may suppress β-catenin and AKT phosphorylation through increased ECAD expression. Indeed, foretinib inhibited angiogenesis, Wnt/β-catenin signaling, and the PI3K/Akt pathway in this study by inhibiting VEGFA, HIF-1α, c-MET, and AKT phosphorylation, as well as CCND1, c-MYC, and β-catenin in c-MET-positive GC.…”
Section: Discussionsupporting
confidence: 59%
“…62 Other study has reported that suppressed EMT through attenuation of AKT phosphorylation and βcatenin. 63 Our results also indicated that foretinib may suppress β-catenin and AKT phosphorylation through increased ECAD expression. Indeed, foretinib inhibited angiogenesis, Wnt/β-catenin signaling, and the PI3K/Akt pathway in this study by inhibiting VEGFA, HIF-1α, c-MET, and AKT phosphorylation, as well as CCND1, c-MYC, and β-catenin in c-MET-positive GC.…”
Section: Discussionsupporting
confidence: 59%
“…The expression of Twist1 was decreased after the transfection of let‐7b mimics in MM cell lines 41 . Overexpression of let‐7 suppressed the production of interleukin‐6 and vascular endothelial growth factor, as well as colony formation in soft agar, in mammary gland epithelium (MCF‐10A) 42 and lung adenocarcinoma (A549) 43 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of serum-circulating exosomal microRNAs revealed a broad increase in miR-373 and miR-200a in patients with ovarian serous adenocarcinoma across all stages (I-IV), while miR-200b and miR200c were more significantly elevated in later stages (III-IV) and correlated with worse survival outcome, suggesting that these microRNAs may differentially modulate EMT/MET shifts during certain EOC progression steps [ 208 ]. Another study [ 209 ] evaluating 2222 total microRNAs from ovarian cancer patient serum samples identified the most stably and markedly downregulated microRNAs as miR-132, miR-26a, and miR-145 (which are known to act as EMT-repressors in other tissue types, as discussed above), as well as let-7b, a microRNA that was recently shown to play multiple anti-tumor roles, including anti-EMT (through attenuation of p-AKT, Twist and β-catenin) and pro-apoptosis in malignant mesothelioma cells [ 210 ]. A 1,170 patient-based meta-analysis of global transcriptome data delineated let-7b as a stratification factor for molecular and clinical classification, and a predictor of poor survival outcome in high grade serous ovarian carcinoma [ 211 ].…”
Section: Factors Contributing To Dynamic Emt Shifts In Ovarian Canmentioning
confidence: 99%